Reaction and performance time of taekwondo top-athletes demonstrating the baldung-chagi - Hermann, G.; Scholz, M.; Vieten, M.; Kohloeffel, M. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to investigate two factors for success in taekwondo competition, the simple reaction time (RT) - beginning with an external signal and ending with a shoulder, hip or ankle movement - and the performance time (PT) - starting of the Baldung-chagi till hitting the target. Subjects were the top 9 athletes from the German National Team. Movements were recorded by 3 infrared cameras of LUKOtronic active marker Motion Capturing System. Seven markers were used, five on the subject (ankle, heel, hip, shoulder, wrist of the kicking side), one trigger marker at the floor, one at the hand-mitt. The average value for the ankle RT is 0.34 sec., 0.26 sec. for hip RT, 0.23 sec. for shoulder RT and 0.31 sec, for PT. A high ankle RT variation, in the range of 0.26 to 0.54 sec, indicates that reducing this variation though training arrangements could improves the probability for success.